Effect of WC or ZrC addition on thermal residual stresses in ZrB2SiC ceramics. (15th November 2016) - Ma, Hai-Bin; Zhang, Guo-Jun; Liu, Hu-Lin; Liu, Ji-Xuan; Lu, Ying; Xu, Fang-Fang
Abstract: The residual stresses in ZrB2 SiC ceramics with the addition of WC or ZrC were measured using Raman spectroscopy (RS) and X-ray diffraction (XRD). The temperatures at which the residual stresses began to accumulate were calculated. The resistance to high-temperature deformation of ZrB2 SiC-based ceramics was evaluated via four-point flexure test under a static load (15, 25 MPa) for 5 h at 1600 °C and 1800 °C. The results indicate that a compressive residual stress existed in SiC particles and a corresponding tensile stress applied in ZrB2 matrix. The values of thermal residual stresses increase in order of ZSZ (ZrB2 SiCZrC) < ZS (ZrB2 SiC) < ZSW (ZrB2 SiCWC). The temperature composite begin to accumulate the residual stresses also increases in the same order. The apparent different behaviors are resulted from their dissimilar grain boundary state and third phase nature in three ceramics. The phenomenon was explained by a proposed model. The results provide a path to design material compositions with an ideal mechanical properties and guidance role for applications. Graphical abstract: Highlights: Residual stresses in ZrB2 SiC with addition of WC or ZrC were measured. High-temperature resistance to deformation of ZrB2 SiC-based ceramics was evaluated. Relationship between mechanical properties and residual stresses was analyzed.